Advanced Country Experiences with Capital Account Liberalization - Bakker, Age (Occasional Papers; Occasional Paper, 2002)
After the industrial countries established current account convertibility in the late1950s, they began to phase out their capital controls. Their efforts were slow and tentative at first, but built up considerable momentum by the 1980s as market-oriented economic policies gained popularity. This paper describes how national policymakers' views of capital controls shifted over time, and how these controls have been closely related to regulation in other policy areas, such as banking and financial markets. As developing countries seek to liberalize their capital accounts to obtain the benefits of increased integration with the global economy, what lessons can be drawn from industrial countries' diverse experiences with capital controls, and how can a country's liberalization measures be sequenced to minimize disturbances to its exchange rate and monetary policies?